Early Twentieth-Century Continental Philosophy - Lawlor, Leonard, 1954- (Book collections on Project MUSE., 2012)
Early Twentieth-Century Continental Philosophy elaborates the basic project of contemporary continental philosophy, which culminates in a movement toward the outside. Leonard Lawlor interprets key texts by major figures in the continental tradition, including Bergson, Foucault, Freud, Heidegger, Husserl, and Merleau-Ponty, to develop the broad sweep of the aims of continental philosophy. Lawlor discusses major theoretical trends in the work of these philosophers-immanence, difference, multiplicity, and the overcoming of metaphysics. His conception of continental philosophy as a unified project.